Democracy and media decadence - Keane, John, 1949- (Cambridge : Cambridge University Press, 2013)
'We live in a revolutionary age of communicative abundance in which many media innovations--from satellite broadcasting to iPhones and electronic books--spawn great fascination mixed with excitement. In the field of politics, hopeful talk of digital democracy, cybercitizens and e-government has been flourishing. This book admits the many thrilling ways that communicative abundance is fundamentally altering the landscape of our lives and our politics, often for the better. But has too little attention been paid to the troubling countertrends, the decadent media developments that encourage concentrations of power without limit, so weakening the spirit and substance of democracy? Exploring examples of clever new methods of government and market censorship, spin tactics and back-channel public relations, John Keane seeks to understand and explain these trends and how best to deal with them. Tackling some tough but fateful questions, Keane argues that'media decadence' is harmful for the democratic body politic'--Publisher description.
Communicative abundance -- Monitory democracy -- Media decadence -- Democracy's opponents -- Why freedom of public communication?
Includes bibliographical references and index.
Keywords: Communication, International -- Social aspects; Communication, International -- Political aspects; Mass media and globalization; Information technology -- Political aspects; Political participation -- Technological innovations; Democracy